Категория археологических находок — бусы (история изучения: основные тенденции и методы, часть 2) - Жиронкина, О. Ю. (Давнина. Харківський історико-археологічний щорічник, 2016)
Summary O. Zironkina. Beads: Category of Аrcheological Finds (History of Study: Major Tendencies and Methods, Part 2) This article is the second part of the historiographic work focused on the analysis of tendencies and methods in the area of ancient beads studies. The first part was published in the collection «LAUREA» (Kharkov, 2007). The historiographic review stresses two major tendencies the studies of ancient beads. Construction of hierarchically organized system, based on one or two principles, is characteristic for the first one; the second one is distinct by the absence of subordination among the type-determining features. The article traces the development of both tendencies mentioned above, starting with publications by G. Eisen, V. A. Gorodtsov, H.C.Beck, and A.V.Artsikhovsky till the present day, including contemporary research involving the most recent mathematical and physicochemical methods (B. Sasse, C. Theune, P. Stadler, R. H. Brill, A. Páбsztor, M. Dekóуwna, etc.).